THE PERCEPTION OF BLACK AND WHITE IN ENGLISH AND ARMENIAN IDIOMS - Avagyan, Naira; Nersisyan, Naira (Armenian Folia Anglistika, 2024)
Colour is a silent language with the help of which people can communicate. It is rich in hidden meanings and symbolisms. We think of colour as an independent concept with a part to play in every aspect of our lives. Colour, as we know, does not exist in the outside world, beyond us, like gravity, protons and oxygen do. Instead, colour is created inside our heads. It is the characteristic of human visual perception. The recognition and interpretation of colour are determined by numerous factors: cultural, religious, spiritual, physiological, and psychological. Colour terms are widely used in phraseological units. Among most common ones are the idioms with the two opposite spectra – colours black and white. The present article discusses the perception of black and white in English and Armenian idioms. The current research is an attempt aimed at revealing the similarities and differences in these two languages through comparative-contrastive and descriptive methods of analysis.
Keywords: colour perception; colour symbolism; idioms; collocations; positive/negative connotation